Malaysian alternative printmaking: a study on style (2000 – 2010) / Mohd Adzman Omar - Omar, Mohd Adzman (2021)
The art of printmaking in Malaysia started when this technique was applied in batik making particularly in the creation of batik sarong using a pre-carved wooden or copper block. The only difference is in the purpose and surface where the image is printed on and how the artists display the artworks. As other countries, Malaysian printmaking also has revolutionized the use of a new concept called unconventional or alternative printmaking. The development of alternative printmaking is considered new in Malaysian contemporary art scene but influence of revolutionized printmaking started when Ponirin Amin produced artwork entitled “Alibi Catur Di Pulau Bidong” (1980). His artwork was considered to be a cross-conventional printmaking discipline. Consequently, the objectives of this study are to trace the chronicles of alternative printmaking in Malaysia, to identify the Malaysian alternative printmakers and to interpret the detailed form, content and context of Malaysian alternative printmaking. In order to obtain information for the study, the researcher had used two methods in this research, method of collecting data and method of analysis. Method of collecting data was divided into two phases; Phase 1 focused on the review of literatures, analysed and presented on the research topic beginning with the significance of the printmakers and their artworks. The study in Phase 2, were carried out in order to identify the artists who are seriously involved in alternative printmaking. In this phase all the data collected were analysed to determine the theme, form, techniques, content and style carried out by the printmakers. The method analysis was divided into two, the formal analysis and contextual analysis, Panofsky theory iconography for formal analysis and Meyer Schapiro theory towards the style in arts for the contextual analysis. The development of style in Malaysian alternative printmaking artists and artwork has been greatly influenced by a few factors as an education, galleries, art collectors and institution. Malaysian have three generations of printmakers who produced alternative printmaking; the pioneer, contemporary printmakers and young artists. Social critics are the famous themes in the production of alternative printmaking compared to cultural, religion and politics.